Mass-guided single-cell MALDI imaging of low-mass metabolites reveals cellular activation markers - Cairns, James L.; Huber, Johanna; Lewen, Andrea; Jung, Jessica; Maurer, Stefan J.; Bausbacher, Tobias; Schmidt, Stefan; Levkin, Pavel; Sévin, Daniel Charles; Göpfrich, Kerstin; Koch, Philipp; Kann, Oliver; et al. (Advanced science, 2025)
Single-cell MALDI mass spectrometry imaging (MSI) of lipids and metabolites >200 Da has recently come to the forefront of biomedical research and chemical biology. However, cell-targeting and metabolome-preserving methods for analysis of low mass, hydrophilic metabolites (<200 Da) in large cell populations are lacking. Here, the PRISM-MS (PRescan Imaging for Small Molecule - Mass Spectrometry) mass-guided MSI workflow is presented, which enables space-efficient single cell lipid and metabolite analysis. In conjunction with giant unilamellar vesicles (GUVs) as MSI ground truth for cell-sized objects and Monte Carlo reference-based consensus clustering for data-dependent identification of cell subpopulations, PRISM-MS enables MSI and on-cell MS2-based identification of low-mass metabolites like amino acids or Krebs cycle intermediates involved in stimulus-dependent cell activation. The utility of PRISM-MS is demonstrated through the characterization of complex metabolome changes in lipopolysaccharide (LPS)-stimulated microglial cells and human-induced pluripotent stem cell-derived microglia. Translation of single cell results to endogenous microglia in organotypic hippocampal slice cultures indicates that LPS-activation involves changes of the itaconate-to-taurine ratio and alterations in neuron-to-glia glutamine-glutamate shuttling. The data suggests that PRISM-MS can serve as a standard method in single cell metabolomics, given its capability to characterize larger cell populations and low-mass metabolites.
Gesehen am 24.03.2025